МАТЕМАТИЧНА МОДЕЛЬ ТЯГОВОГО АСИНХРОННОГО ДВИГУНА З УРАХУВАННЯМ НАСИЧЕННЯ - Кулагін, Д.О. (Інститут електродинаміки НАН України, Київ, 2014)
On the basis of a method of dynamic inductances a mathematical model of asynchronous traction motor, which takes into account the tangential and radial dynamic inductances. The use of this method has allowed to take into account the saturation of the main magnetic path, saturation flow path, scattering, inter induction caused by saturation of between circuits of the machine, as well as joint saturation work flow and flows of scattering for modes that are characterized by significant amount of work flow and large values of current circuits of the machine. The result was recorded in (d,q) coordinate system of equations of circles asynchronous traction motor taking into account the saturation. References 14, figures 2.